Analysis Of Maturity Assessment Of Government Internal Control Systems - Romi Samiaji; Liez Zulfiati; Nursanita Nasution (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Abstract—This study aims to assess the maturity of the government internal control system in the Ministry of Foreign Affairs of the Republic of Indonesia in 2018 and to determine what strategies should be carried out by the Ministry of Foreign Affairs of the Republic of Indonesia in improving the maturity assessment of the government's internal control system in the following year. This research method is a descriptive method using secondary data. Secondary data used in this study are supporting documents obtained at the time of validating the maturity assessment of the government's internal control system in the Ministry of Foreign Affairs of the Republic of Indonesia in 2018. Data Analysis Methods used in this study are in accordance with the Head of the Financial and Development Supervisory Agency Republic of Indonesia No. 4 of 2016 concerning Guidelines for Appraisal and Maturity Improvement Strategy of the Government Internal Control System. In total, there are five assessment focuses that are distributed into 25 SPIP sub-elements according to the Regulation of the Head of the Indonesian Financial and Development Supervisory Agency No 4 of 2016. The results of this study indicate that the conditions of applying the Internal Control System practices at the Ministry of Foreign Affairs of the Republic of Indonesia in 2018 reached the category of "Managed and Measured" with a score of 4.0. Managed and measurable level means that the Ministry of Foreign Affairs of Indonesia has implemented effective internal control. Each personnel implementing the activity always controls the activities on achieving the objectives of the activity itself and the objectives of the Ministry of Foreign Affairs of the Republic of Indonesia. Evaluation is done formally and documented. However, most evaluations are done manually, not yet using a computer application assistance tool.